Additional records and new synonyms of Cicindelidae and Carabidae (Coleoptera) from the lsland of Sakhalin in the Russian Far East - Sh. Lafer, German; Nilsson, Anders; Kholin, Sergey (Entomologica Fennica, 1997)
Faunistic records of three cicindelid and 47 carabid beetle species are given for the Island of Sakhalin in the Russian Far East. Most records refer to a material collected in 1993 and 1994 in SW Sakhalin by the two junior authors. The following five carabid species are here reported from Sakhalin for the first time: Bembidion chloropus Bates, Pterostichus neglectus A. Morawitz, Agonum jankowskii Lafer, A. piceum (Linnaeus) and Microlestes minutulus (Goeze). The gross distributions of all mentioned species are given, with special emphasis on the Far East. The following syn. nov. are given: Pterostichus (Euryperis) eximius A. Morawitz, 1862 (= crassiceps A. Morawitz, 1862; = rudnicus Jedlicka, 1938; = obliquebasalis Jedlicka, 1962; = prochazkorum Jedlicka, 1967; = sakhalinensis Kirschenhofer, 1985).